O papel da radiografia panorâmica como método auxiliar no diagnóstico precoce de osteoporose em mulheres na pós-menopausa - Carmo, Juliana Zigart Brum (2017)
To examine the role of panoramic radiographs in the diagnosis of osteoporosis in postmenopausal women. This cross-sectional study included 198 volunteer postmenopausal women over 40 years of age recruited at the Climacteric Outpatient Clinic of the Júlio Muller University Hospital of UFMT, Cuiabá-MT between 2014 and 2015. Panoramic radiographs were evaluated through a validated program (Radiocef Studio 2, version 2.0). Two aspects were analyzed in the mandibular panoramic radiograph: one qualitative, referring to the shape of the mandibular cortical plate, and other quantitative, referring to the width of the mandibular bone cortex. The morphology of the mandibular cortical bone was determined by observing the region between the bilateral mental foramen and cortical categorized it into three groups. Bone densitometry was verified in the lumbar spine and femur. There was good agreement between mental index and bone mineral density in the lumbar spine (Kappa = 0,718); regarding the femoral neck, the agreement between both methods was moderate (Kappa = 0,443). A bettler degree of concordance occurred when the mandibular cortical index (CMI) was compared with the bone mineral density of the lumbar spine (Kappa = 0,912). CMI and bone mineral densitometry also showed good agreement in the femoral neck (Kappa = 0,579). Conclusion: The radiomorphometric indexes evaluated wing mandibular panoramic radiographs presented moderate to good agreement with bone mineral densitometry.Panoramic radiographys are capable of identifying postmenopausal women with low bone mineral density and can be used to refer them for appropriate medical and odontological treatment.